DETERMINANTS OF PRIVATE AGRICULTURAL INVESTMENT IN IRAQ FOR THE PERIOD (1990-2014) - & Hmzah, Ahmad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The agricultural sector is one of the important economic sectors which contribute to provide the food and raw materials that use into many industrial goods and create jobs. Moreover, it helps to reduce the imports of agricultural products and activate of growing the other manufacturing sectors. Even though, the agricultural is very important sector, but still weak and unworthy because the agriculture produce line is not flexible to aggregate demand; however, it needs to expansion in agricultural investment. Since the agricultural sector has characters which are quite different than other sectors which are effective on investor's decisions rely on the economic policy. The study aim to determine the impact of the GDP, interest rate, inflation, exchange rate and conception government expenditure on agricultural privet investment. The study used time series data from (1990-2014) with Autoregressive Distributed Lag (ARDL) as a model .The result showed the long run relationship between privet investment and its determents. The adjustment coefficient is negative and significant at 1%, and gross domestic product is positive impact on investment, while the impact of  the other variables are negative in agricultural investment. The study recommends increasing the investment expenditure on scientific agricultural researches, especially, on the assets productivity of animals, seeds and plants; however, it has to consider the impact of some elements of fiscal and monetary policy which is needed to stimulate private agricultural investment.